2018
DOI: 10.1186/s13068-018-1224-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a hyperthermophilic endoglucanase in hybrid poplar modifies the plant cell wall and enhances digestibility

Abstract: BackgroundExpression of glycosyl hydrolases in lignocellulosic biomass has been proposed as an alternative to improve efficiency of cellulosic ethanol production. In planta production of hyperthermophilic hydrolytic enzymes could prevent the detrimental effects often seen resulting from the expression of recombinant mesophilic enzymes to plant hosts. Utilizing lignocellulosic feedstocks to produce hyperthermophilic hydrolases provides additional benefits for ethanol production in the way of transgenic feedstoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Reduced recalcitrance of plant biomass by in planta expression of E1cd and other CWD enzymes has been shown in many previous reports (Brunecky et al, 2011; Chou et al, 2011; Chung et al, 2015; Donohoe et al, 2017; Klose et al, 2015; Mir et al, 2017; Xiao et al, 2018). It has been demonstrated that the decreased recalcitrance was not due to the postpretreatment residual enzyme activity.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Reduced recalcitrance of plant biomass by in planta expression of E1cd and other CWD enzymes has been shown in many previous reports (Brunecky et al, 2011; Chou et al, 2011; Chung et al, 2015; Donohoe et al, 2017; Klose et al, 2015; Mir et al, 2017; Xiao et al, 2018). It has been demonstrated that the decreased recalcitrance was not due to the postpretreatment residual enzyme activity.…”
Section: Resultsmentioning
confidence: 64%
“…Alternatively, key cell wall‐depolymerizing (CWD) enzymes, such as a cellulase or xylanase, have been introduced into plants to improve postharvest biomass processability (Brunecky et al, 2011; Chou, Dai, Hsieh, & Ku, 2011; Donohoe et al, 2017; Klose, Roder, Girfoglio, Fischer, & Commandeur, 2012). This would allow the biomass feedstocks to serve as both enzyme suppliers and substrates for ethanol production (Xiao, He, Ojeda‐Lassalle, Poovaiah, & Coleman, 2018). To avoid detrimental effects on the growth of plant hosts, thermophilic or hyperthermophilic enzymes are often used for expression in planta.…”
Section: Introductionmentioning
confidence: 99%
“…Plants can be more suitable for the production of exocellulases than microorganisms due to the higher enzyme activity (Klinger et al 2015). Endoglucanases can be secreted to the apoplast (Xiao et al 2018), but targeting to the ER (Klose et al 2015) or plastids (Schmidt et al 2019b;Fumagalli et al 2019) helps to prevent the enzymes degrading essential cellulose structures before plants are harvested and homogenized for product extraction. Alternatively, enzyme expression can be restricted to specific organs, such as maize kernels (Vicuna Requesens et al 2019), or can be induced at a particular time, such as just before harvest, thus reducing the fiber content and rigidity, which can facilitate primary product extraction.…”
Section: Self-catalyzed Processing Of Residual Biomassmentioning
confidence: 99%
“…Such transgenic approaches have not only produced favorable phenotypes for industrial processing, but have resulted in plants with novel SCW properties as well as additional traits such as increased stress tolerance. Self-processing plants with increased industrial processing efficiency and biotic defense responses are generated by in planta expression of xylan targeting CWDE from wood rotting fungi that can be active under normal plant growth (Gandla et al, 2014; Pawar et al, 2017b), or only become active upon application of external stimulus (Shen et al, 2012; Mir et al, 2017; Xiao et al, 2018; Table 1). Various studies have shown that xylan modifications differ between plant species and lineages (Allerdings et al, 2006; Rennie and Scheller, 2014; Peña et al, 2016; Smith et al, 2017; de Souza et al, 2018) and modification genes from one lineage can add modifications to the xylan backbone of another (Anders et al, 2012; Xiong et al, 2015; Zhong et al, 2018; Table 1).…”
Section: Biorefinery Associated Industrial Processesmentioning
confidence: 99%